Ireland's recent productivity performance - O'Toole, Ronnie (Statistical and Social Inquiry Society of Ireland, 2005)
This paper examines the reasons for the recent divergence in US and European productivity performance. The paper shows that the structure of European industry is ill suited to the challenge of innovation which has to be faced given the rapid development of ICT technology and the fact that the ability to grow economically by imitating US innovation becomes more limited as convergence to US levels of output is approached. Turning to Ireland, the paper will show that while Ireland?s productivity growth over the last decade has been impressive, we still compare unfavourably with Europe when adjustment is made for transfer pricing. Much of Ireland?s economic success has been through the employment of more resources, not their greatly improved utilisation. Further, the persistent problems of Irish per capita productivity stem from the well-known deficiencies of Irish public services, and the less appreciated failures of ICT-using services, particularly retail sales. Finally, the paper argues that Ireland exhibits greater cultural preference for (voluntary) leisure than our European neighbours.
Barrington lecture 2004/2005
Read before the Society, 29 March 2005
Keywords: Productivity growth; Comparative productivity; Irish per capita productivity; 314.15